IMPLEMENTASI INOVASI DAERAH DI KOTA BALIKPAPAN - Irfan Setiawan (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2017)
Implementation of smartcity in the city of Balikpapan is a challenge for governance that aims to provide the welfare of the community. Innovation are developed through the application of the concept of smartcity is still recently implemented and is still fairly new, but the application already indicates the serious intention of the city government to provide ease of information and services needed by the community. With the application of technology in the service to the community, of course the role and duty of the local government of the city will be helped and also the goal of the city government to provide excellent service to the public in order to realize the smart government will be achieved.